Zwicknia gattolliati, a new species of stonefly from Italy (Plecoptera: Capniidae) - Vinçon, Gilles; Reding, Jean-Paul G. (Zootaxa, 2018)
A new species of Zwicknia Murányi, Z. gattolliati, from northern Italy and from the Italian Abruzzo Region is described and illustrated on the basis of the morphology of male and female adults and previous molecular and drumming studies.